The Identity of the Church as Civitas Dei: An Analysis of Augustine's Political Philosophy in the Indonesian Bishops' Conference's Response to Political Dynamics in Indonesia in 2025 - Agustinus Abraham (International Perspectives in Christian Education and Philosophy, 2026)
This study examines the identity and role of the Catholic Church as civitas Dei through an analysis of Augustine of Hippo’s political philosophy and its relevance to the pastoral response of the Konferensi Waligereja Indonesia (KWI) toward Indonesia’s socio-political dynamics in 2025. The research departs from the problem of how the Church should position itself amid political polarization, violent demonstrations, and violations of human dignity that marked the national context. It aims to (1) explain Augustine’s concept of civitas Dei and civitas terrena, (2) formulate the Church’s identity as a moral-spiritual community oriented toward God, and (3) analyze the relevance of this framework for the Church’s prophetic and pastoral engagement in Indonesia. This study employs a qualitative method with a literature review approach, drawing from Augustine’s De Civitate Dei, Church documents, and the official pastoral statement of KWI, complemented by relevant theological and socio-political sources. The findings show that Augustine’s distinction between the two cities is not merely institutional but based on the orientation of love: love of God that generates justice and service, versus self-love that leads to domination and injustice. Within this framework, the Church in Indonesia actualizes civitas Dei through solidarity with victims, ethical criticism of power, and active participation in promoting peace and the common good. KWI’s pastoral statement embodies this prophetic stance by advocating nonviolence, human dignity, and social justice. In conclusion, Augustine’s political theology remains normatively relevant for guiding the Church’s mission as a transformative moral force in contemporary public life.